Covid-19 Vaccination: Health and Economic Correlations - Zaky Musyarof; Indira Nur Qomari (Proceedings of The International Conference on Data Science and Official Statistics, 2021)
Vaccination program is an important strategy in eradicating Covid-19 pandemic. Vaccination can intervene to accelerate the formation of herd immunity. When herd immunity is formed later, it is believed that the Covid-19 virus will gradually eradicated. Furthermore, economic activity will return to normal. Then, has the vaccination program run by the Indonesian government had an impact on health and economic recovery? Some claim that this vaccination program has had a positive impact. However, in-depth research is felt to be done to really look at this impact. As a first step, it is necessary to look at the relationship between vaccination, health and economic development. This relationship will be an early indication of whether the vaccination program is successful or not. In fact, vaccination was strongly correlated with a decrease in the transmission of new cases and moderately correlated with the recovery rate. Overall, vaccination is strongly correlated with health based on the canonical correlation. Meanwhile, for the economy, vaccination has a weak correlation with the poverty rate and Gini ratio. However, overall based on the canonical correlation, vaccination is strongly correlated with the economy. Furthermore, the development of tourism shows an indication of a correlation with vaccination.